Modeling and simulation of DC to DC boost converter using single phase matrix converter topology - Fajariah Kadir; S.Z. Mohammad Noor; Faranadia A.H.; K.S. Muhammad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The main objective of this work is to model and simulate DC to DC Boost Converter using Single Phase Matrix Converter (SPMC) topology using MATLAB/Simulink (MLS). The output voltage is controlled by using Pulse Width Modulation (PWM) technique. Four pairs of Insulated Gate Bipolar Transistor (IGBT) is used as the switching device where for each pair, it is located in parallel and opposite direction. Safe commutation technique is performed in preventing voltage spike at the output. Through the simulation, at switching frequency of 25kHz, the model is able to step up its input voltage about two times larger and all of the results achieved a good agreement with the principle of four quadrant operation. It is also realized that without the implementation of safe commutation technique, spikes were generated and the model is unable to boost its input voltage. All of the selected results from the analysis which includes variation of quadrant, switching frequency, duty cycle and resistive load are presented in this paper.